Risk assessment and management of chemical hazards for pregnant workers: a qualitative review of guidance from EU member states - Thomas Claessens; Karin Sørig Hougaard; Steven Ronsmans (Journal of Occupational Medicine and Toxicology)
Abstract Background Exposure to workplace chemicals can pose serious risks to reproductive health. The European Union’s Pregnant Workers Directive requires risk assessments but lacks clear guidelines for assessing chemical reproductive hazards in workplaces. Aims This study aims to review how EU member states implement the Pregnant Workers Directive by analysing national guidance documents and relevant literature. Methods A qualitative review was conducted, combining a systematic literature search with outreach to EU national experts to gather relevant guidance documents. Thematic synthesis identified guiding principles for implementing maternity protection for chemical exposures. Results Two main themes were identified: the need for a broad perspective and for certainty in risk assessment. The broad perspective stresses the importance of considering all reproductive hazards, not limited to those listed in the EU Directive and inclusion of male workers and the preconception period, and the potential adverse socio-economic consequences of applied protective measures. The need for certainty highlights the challenges in reliable risk assessments, due to lack of knowledge about chemicals’ hazardous properties, dose-response relationships and the level of worker exposure. These themes reveal the complexity of implementing effective maternity protection and the need for improved guidelines across the EU. Conclusions This study calls for a unified approach to reproductive health protection, extending beyond pregnancy to include also preconception and paternal exposures. The findings highlight the need to support practitioners in the risk assess process at workplaces in the EU by providing a framework for the assessment of reproductive hazards and determining protective measures.